Political Analysis Of Prabowo Subianto's Branding Through Instagram Social Media @Prabowo: Case Study Of The 2024 Election Campaign - Atala Atala; Muhammad Prakoso Aji (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
This journal will analyze Prabowo Subianto's political branding strategy during the 2024 election campaign period through Instagram social media. This research review through descriptive qualitative research method explores how the Prabowo Subianto campaign's social media team managed to package interesting content on Instgaram as an effort to form a positive political branding or image for Prabowo Subianto. This research review through descriptive qualitative research method explores how the Prabowo Subianto campaign's social media team managed to package interesting content on Instgaram as an effort to form a positive political branding or image for Prabowo Subianto. The target of the campaign team, especially the social media team, is young voters or Generation Z, which are the first voters in the 2024 elections, so campaign content must be interesting and innovative. The research shows that Prabowo Subianto's success in winning the 2024 election was achieved through digital campaigns on social media, especially Instagram. The use of the term "gemoy" was naturally born from netizens, not from Prabowo Subianto's campaign team. Humanistic interactions have attracted positive sentiment, even though @prabowo's Instagram has the fewest posts compared to his competitors. The uniqueness of Instagram posts has successfully shaped branding through relatable visuals and narratives that make Prabowo Subianto stand out through the unique popularity of the nickname "gemoy". The research shows that the public debate also influenced the increase in Prabowo Subianto's followers on Instagram due to his positive performance in the debate. This research underlines that social media as an effective tool for modern political campaigns and consistent branding that creates emotional closeness with voters can increase voter trust. This is in line with the theory used in this research, namely the theory of political branding by Bruce Newman, specifically discussing four aspects of success in shaping the political branding of a candidate or political party.